microRNA 181a regulates IFN-γ expression in effector CD8+T cell differentiation - Amado, Tiago (2020)
In the past years, the importance of microRNAs in the development and maintenance of cell identity and on the regulation of cytokine expression within cells of the immune system has gained increasing strength. CD8+ T cells are key players in immunity against intracellular infections, namely viral infections, and tumors. The main cytokine associated with these protective responses is interferon-IFN-γ, whose production is known to be regulated at the transcriptional level during CD8+ T cell differentiation. In this study, we show that microRNAs constitute a post-transcriptional brake to IFN-γ expression by CD8+ T cells as the genetic interference with the Dicer processing machinery resulted in the increased production of IFNγ by both thymic and peripheral CD8+ T cells. Using a YFP reporter mouse for IFN-γ locus activity we compared the microRNA repertoires associated with the presence or absence of IFN-γ expression. This allowed us to identify a set of candidates, including miR-181a and miR-451, which were functionally tested in overexpression experiments using synthetic mimics in peripheral CD8+ T cell cultures. We found that miR-181a limits IFN-γ production by suppressing the expression of the transcription factor Id2, which in turn promotes the Ifng expression program. Importantly, upon MuHV-4 challenge, miR-181a-deficient mice showed a more vigorous IFNγ+ CD8+ T cell response, and were able to control murid gammaherpesvirus-4 virus infection significantly more efficiently than control mice. Collectively, these data establish a novel role for miR-181a in regulating IFN-γ–mediated effector CD8+ T cell responses in vitro and in vivo.